The horizontal reactive media treatment well (HRX Well®) for passive in situ remediation: Design, implementation, and sustainability considerations. Issue 4 (6th September 2018) - Divine, Craig E.; Wright, Jesse; Wang, Jack; McDonough, Jeff; Kladias, Michael; Crimi, Michelle; Nzeribe, Blossom N.; Devlin, J.F.; Lubrecht, Michael; Ombalski, Daniel; Hodge, Billy; Voscott, Hoa; et al.
Abstract: A new in situ remediation concept termed a Horizontal Reactive Media Treatment Well (HRX Well ® ) is presented that utilizes a horizontal well filled with reactive media to passively treat contaminated groundwater in situ. The approach involves the use of a large‐diameter directionally drilled horizontal well filled with solid reactive media installed parallel to the direction of groundwater flow. The engineered contrast in hydraulic conductivity between the high in‐well reactive media and the ambient aquifer hydraulic conductivity results in the passive capture, treatment, and discharge back to the aquifer of proportionally large volumes of groundwater. Capture and treatment widths of up to tens of feet can be achieved for many aquifer settings, and reductions in downgradient concentrations and contaminant mass flux are nearly immediate. Many different types of solid‐phase reactive treatment media are already available (zero valent iron, granular activated carbon, biodegradable particulate organic matter, slow‐release oxidants, ion exchange resins, zeolite, apatite, etc.). Therefore, this concept could be used to address a wide range of contaminants. Laboratory and pilot‐scale test results and numerical flow and transport model simulations are presented that validate the concept. The HRX Well can access contaminants not accessible by conventional vertical drilling and requires no aboveground treatment or footprint and requires limited ongoing maintenance. A focused feasibility evaluation and alternatives analysis highlights the potential cost and sustainability advantages of the HRX Well compared to groundwater extraction and treatment systems or funnel and gate permeable reactive barrier technologies for long‐term plume treatment. This paper also presents considerations for design and implementation for a planned upcoming field installation.